PENERAPAN METODE OUTDOOR STUDY PADA MATAKULIAH PEMBELAJARAN IPA SD UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF MAHASISWA - Aldino Aldino; Arisman Sabir; Antok Kurniawan; Septian Raibowo (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research aims to describe improving students' cognitive abilities using the outdoor study method in elementary science learning This research is Classroom Action Research (CAR) using a combined qualitative and quantitative approach (mixed method). This data collection technique is based on observation and tests sourced from lecturers and students at Muara Bungo Muhammadiyah University. This research was carried out in two cycles, with four stages, namely planning, implementation, observation, and reflection. The research results show that applying the outdoor study method can improve students' cognitive abilities. The achievement of student learning outcomes proves this before applying the outdoor study method in the learning process which can be said to be still low with an average score of 50 with a learning completion percentage of 28.6%. By applying the outdoor study method to the learning process it shows an increase in the first cycle; an average score of 69.28 was obtained, with the percentage of student learning completeness increasing to 66.7%, and in the second cycle, the average score was 80.0 with the student learning completion percentage being 95.2%. Based on the results of this research, it can be concluded that applying the outdoor study method in elementary science learning can improve students' cognitive abilities. This is proven by an increase in student learning activities and an increase in the percentage of student learning completion at each meeting.